Combustion Synthesis Porous Nitinol for Biomedical Applications - H. Aihara; J. Zider; G. Fanton; T. Duerig (International Journal of Biomaterials)
Porous Nitinol with a three-dimensional anisotropic interconnective open pore structure has been successfully produced by the combustion synthesis (CS) of elemental Ni and Ti powders. The resulting product can be tailored to closely match the stiffness of cancellous bone to minimize stress shielding. The average elastic modulus was approximately 1 GPa for a porosity of 60 vol% and the average pore size of 100-500 µm. The low elastic modulus meets the basic demand for orthopedic bone ingrowth applications. Furthermore, porous Nitinol was composed of cubic (austenitic) and monoclinic (martensitic) NiTi compounds without the presence of Ni metal or Ni-rich phases. The resulting product exhibits excellent corrosion resistance with breakdown potentials above 750mV. An ovine study in cortical sites of the tibia demonstrated rapid osseointegration into the porous strucutre as early as two weeks and complete bone growth across the implant at six weeks. A separate ovine study showed complete through-growth of bone at four months using a lumbar interbody fusion model, substantiating the use of porous Nitinol as an implant material for applications in the spine. Porous Nitinol is thus a promising biomaterial with proven biocompatibility and exceptional osseointegration performance which may enhance the healing process and promote long-term fixation, making it a strong candidate for a wide range of orthopedic implant applications.